Perbedaan Tingkat Self Regulated Learning Siswa Sekolah Menengah Pertama di Masa Pandemi Ditinjau Dari Jenis Kelamin - Istiqomah, Intan Wahyu; Faruq, Faruq; Sabani, Nureyzwan; Rahmawati, Siti; Rivalna, Kelvin; Kumaidi, K; Sudinadji, Muh Bagus (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
This study aims to identify the level of self-regulated learning of male and female studentsin junior high schools (SMP) in the residency of Surakarta. This quantitative studyinvolved 223 students consisting of 115 male students and 108 female students as theresearch subjects. The instrument used is the Self-regulated Learning Scale which wasdeveloped based on aspects of Zimmerman's theory with the results of the validity testusing a CVI of 0.68 to 1.00 and a reliability test with a Cronbach alpha value of 0.893. Thedata analysis method used in this study is Non Parametric with the Mann-Whitney Test.The results showed that there was a significant difference between the self-regulated learning of male students and female students during the pandemic period, the self-regulated learning of female students was higher than male students.